2004
DOI: 10.1007/s00442-004-1503-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of tree dieback in Queensland, Australia: the importance of drought stress and the role of resistance to cavitation

Abstract: During the extreme 1992-1997 El Niño drought event, widespread stem mortality, or tree "dieback", of both mature and juvenile eucalypts occurred within the tropical savannas of northeast Australia. Most of the dieback occurred in individuals of the ironbark species complex ( Eucalyptus crebra- E. xanthoclada) while individuals of the bloodwood species Corymbia erythrophloia, exhibited significantly less stem mortality. Indicative of greater water stress, predawn and midday xylem water potentials of ironbark ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
2
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 33 publications
4
92
2
7
Order By: Relevance
“…Rice et al (2004) reported that during the extreme 1992-1997 El Niñ o drought period in Queensland, Australia, tree species with greater resistance to xylem cavitation showed the most dieback, which they attributed to shallower root systems. In response to a record drought in 2007 in central North Carolina, USA, tree species with the greatest resistance to cavitation showed the greatest canopy dieback (Hoffmann et al 2011), which the authors attributed both to greater leaf retention and shallower root systems in the cavitation-resistant species.…”
Section: Discussionmentioning
confidence: 99%
“…Rice et al (2004) reported that during the extreme 1992-1997 El Niñ o drought period in Queensland, Australia, tree species with greater resistance to xylem cavitation showed the most dieback, which they attributed to shallower root systems. In response to a record drought in 2007 in central North Carolina, USA, tree species with the greatest resistance to cavitation showed the greatest canopy dieback (Hoffmann et al 2011), which the authors attributed both to greater leaf retention and shallower root systems in the cavitation-resistant species.…”
Section: Discussionmentioning
confidence: 99%
“…However, hydraulic failure is difficult to trace in the field. Lower resistance to cavitation (Rice et al 2004) and lethal leaf dehydration (Kursar et al 2009) have been related to increased mortality in other species, rendering hydraulic failure a very plausible mechanism for observed tree mortality under severe, acute drought. A drawback of the EDM is that well-documented system tip-outs are sparse in space and time; therefore, such models are based on local data.…”
Section: Performance Of the Edmmentioning
confidence: 99%
“…Therefore, the first basal area increment value in our time series is: BAI1= BA1 − BA0 = π × (RadIB − CL + TRW1) 2 − π × (RadIB -CL) 2 ; the second one is:…”
Section: Dendrochronology and Drought Sensitivitymentioning
confidence: 99%